Machine learning-based prediction of ambient CO2 and CH4 concentrations with high temporal resolution in Seoul metropolitan area - Seongjun Park; Kwang-Joo Moon; Hyo-Jin Eom; Seung-Muk Yi; Youngkwon Kim; Moonkyung Kim; Donghyun Rim; Young Su Lee (Environmental Pollution, 2025)

Reduction of potentially toxic elements content of dried laver Pyropia spp. using ultrasonic treatment - Kil Bo Shim; Yeon Joo Bae; Jong Bong Lee; Ga Yeon Kwon; Hyo Rim Lee; Suk Kyung Shon; Hyeong Jun Kim; Min Jae Kim; Ha Eun Park (Food Chemistry, 2025)

Effect of activated carbon-based two-stage adsorption on biogenic amine reduction and quality of anchovy fish sauce at industrial scale - Jung-Jin In; Kil Bo Shim; Jong Bong Lee; Yeon Joo Bae; Ga Yeon Kwon; Hyo Rim Lee; Sunhyun Park; Suk Kyung Sohn (Food Chemistry, 2024)

Estimation of Genetic Parameters and Optimum Breeding Programme Design in Korean Flatfish Breeding Population - Phuong Thanh N. Dinh; Jong-Won Park; Waruni Ekanayake; Yeongkuk Kim; Dooho Lee; Dain Lee; Hyo Sun Jung; Julan Kim; Hye-Rim Yang; Heegun Lee; Sangwon Yoon; Jeong-Ho Lee; et al. (Fishes, 2022)
Olive flounder (Paralichthys olivaceus) is a vital aquaculture species in East Asia. However, few studies that estimate the genetic parameters of this species have been conducted. We estimated the genetic parameters of growth traits and designed an optimum breeding programme for this species. Heritability, genetic and phenotypic correlations, and breeding values were estimated for growth traits: body weight (BW), total length (TL), and condition factor (CF). A linear mixed animal model using the restricted maximum likelihood (REML) algorithm was applied to the statistical analysis of 9 traits (BW, TL, and CF at 11, 18, and 22 months of age) for a total of 54,159 animals from 7 generations. Increases of 13%, 8%, and 6.5% in BW, TL, and CF at the harvest stage were observed, respectively, after 7 generations of selection. The heritabilities of all growth traits were moderate, ranging from 0.35 to 0.46. The phenotypic and genetic correlations between BW and TL were high and positive in all three stages (0.91 and 0.92, 0.91 and 0.93, and 0.88 and 0.91). The estimated breeding values of BW and TL increased over the generations; however, the estimated breeding value of CF fluctuated. The optimum progeny number within full-sib families for an accuracy of 0.632 is suggested to be between 10 and 25. Findings indicated that a considerable response to selection and single-trait selection based on BW would be effective in olive flounder.

Cardiac adaptation to exercise training in health and disease - Dae Yun Seo; Hyo-Bum Kwak; Amy Hyein Kim; Se Hwan Park; Jun Won Heo; Hyoung Kyu Kim; Jeong Rim Ko; Sam Jun Lee; Hyun Seok Bang; Jun Woo Sim; Min Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2020)

Identification of the Aggregation-sex Pheromone Produced by Male Monochamus saltuarius, a Major Insect Vector of the Pine Wood Nematode - Hyo-Rim Lee; Sung-Chan Lee; Dong Ha Lee; Won-Sil Choi; Chan-Sik Jung; Jae-Ho Jeon; Jeong-Eun Kim; Il-Kwon Park (Journal of Chemical Ecology, 2017)

Hairy root induction in Oriental melon (Cucumis melo) by Agrobacterium rhizogenes and reproduction of the root-knot nematode (Meloidogyne incognita) - Hyo-Kyung Pak; Joon-Soo Sim; Yong Rhee; Hyo-Rim Ko; Sun-Hwa Ha; Mun-Sup Yoon; Chan-Ho Kang; Sukchan Lee; Yong-Hwan Kim; Bum-Soo Hahn (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)